ODEL KELEMBAGAAN PEMBANGUNAN KAWASAN ANDALAN TOLITOLI - warseno, warseno (Badan Pengkajian dan Penerapan Teknologi, 2007)
Institution is an important aspect for creating strategy of the pledge area development. Regarding the implementation of the strategy, some aspects have to be highlighted such as (1) the strategy has to be a guideline for the organization daily routine; (2) the strategy and the organization have to be united, means the strategy has to be reflected the way of running the organization, or implementing the visions and missions as well; (3) therefore, by using the strategy it is compulsory for the decision makers to direct and to control both the process and the result of the activities, and to be flexible in any circumstances. In order to be implemented effectively, institutionalization of the strategy development in astrategic planning is a must that means the strategy has to be built in the organization daily routine. Four main instruments which can be used for institutionalized the strategy respectively are: the organization structure, the leadership, the suitability of the organization strategy and culture, and the organization’s reward system.